(untitled) (Interdisciplinary Studies Journal, 2024)
This work explores the importance of children’s active participation in the construction of the early childhood education curriculum, highlighting the power relations and social dynamics that influence this process. Thus, the objective was to analyze the literature on the effective participation of children in the early childhood education curriculum, with an emphasis on curricular practices and discussions on the sociology of childhood. To achieve this objective, a qualitative methodological approach was adopted, using the integrative literature review as the main research method. Relevant articles, books and theses from the last two decades were selected, obtained from databases such as Scielo and Google Scholar. To do this, we base ourselves on Apple (2006), Ariès (1981), Arroyo (2013; 2017), Corsaro (2011), Giroux (1997), Heywood (2004), Kohan (2004; 2009), Monteiro (2014; 2019), Oliveira-Formosinho (2004; 2019), Sacristán (2000; 2010), Sarmento (2003; 2005; 2007), Zabalza (1998; 2001), among others. The results indicate that children’s participation in the curriculum is still limited by historical and cultural power relations that marginalize children. However, participatory pedagogical approaches that value children’s experiences and perspectives can promote a more inclusive and equitable educational environment.